Design and Optimization of Metal Matrix Composite (MMC’S) Spur Gear - Purushottam Karthik Janaswamy; Rohith Sai Tunuguntla; Sai Praneeth Singu (International Journal of Advanced Design and Manufacturing Technology, 2017)
Gears are one of the most critical components in power transmission system of an automobile and also many rotating machinery. Many studies have been conducted on optimum gear design. The main objective is to design different aluminium metal matrix composite spur gears before and after optimization. Aluminium metal matrix material composites are preferred mostly due to their low density. Also the high specific mechanical properties make these alloys one of the most interesting material alternatives for the manufacture of lightweight parts for many types of vehicles. With wear resistance and strength equal to cast iron, 67% lower density and three times thermal conductivity, aluminium MMC alloys are ideal materials for the manufacture of lightweight automotive and other commercial parts.  In the present work materials considered are Al 6061-T6, Al 6106-T6, Al 7075-T651, and Al 7050-T7451. Finite Element Analysis is performed on different spur gears using above materials and the results will be compared.